Teenagers and videoconference fatigue: a preliminary analysis from an affordance-based approach - Lee, Chei Sian (2024)
The Covid-19 pandemic has led to the widespread use of videoconference (VC) technologies, particularly in education and this trend is projected to continue. Prolonged VC usage can lead to “videoconference fatigue” (VCF). While research on factors contributing to VCF has been conducted among university students, there is limited research on younger students (especially teenagers). To fill this gap, this study adopts an affordance-based approach to identify VC affordances (resources and constraints) contributing to VCF in teenagers. Specifically, the objectives are to examine if (a) VC affordances (visibility, information, and availability), and (b) demographic profiles (age and gender) have effects on VCF among teenagers. A large-scale survey was conducted and responses from 491 teenagers were analyzed using Hierarchical Regression Analysis. Results indicate that the three identified VC affordances contribute to VCF in teenagers. In addition, teenage girls and older teenagers are more prone to VCF.